The Impact of the Demographic Ice Age on Economic Growth, Public Policy, and the Sustainability of Pension Systems - Barta, Judit; Novoszáth, Péter (Demographic Challenges in Central Europe: Legal and Family Policy Response, 2024)
Over the past decades, the demographic conditions of European countries have been characterised by decreasing fertility rates and, consequently, fewer births and an ageing society. The Member States of the European Union face similar demographic problems, with the number of births stagnating or decreasing and the total fertility rate falling beneath the 2.1 value necessary for the simple reproduction of the population. The European Union does not have a family policy, and the Member States deal with the challenges arising from the ‘demographic ice age’ through different methods at the national level, taking into account their countries’ different needs and cultural backgrounds, and especially their ever-shrinking financial possibilities, with little success. This chapter analyses in detail the effects of demographic changes on economic growth, labour markets, monetary policy, budgetary and other government policies, and, ultimately, the sustainability of pension systems and retirement livelihoods. The chapter attempts to demonstrate that a coherent family policy and other related government policies could have a positive effect on the current unfavourable demographic processes within individual countries, as well as on their expected negative consequences, if they were to focus on the demographic challenges in a meaningful way. The conditions in Hungary are described, in addition to international trends. Keywords: Economic theory of fertility, family policy, demographic winter, demographic ice age, family benefits, family policy, fertility rate, number of live births, pension system, minimum pension, supplementary pension, old age